Empowering Learning: Pedagogical Strategies for Advancing 21st Century Skills and Quality Education - Moses Adeleke Adeoye; Entika Fani Prastikawati; Yusuff Olatunji Abimbowo (Journal of Nonformal Education, 2024)
The United Nations Sustainable Development Goal 4 (SDG 4) underscores the significance of quality education for all, emphasizing the want for inclusive and equitable learning opportunities that vend lifelong learning and the acquisition of essential capabilities. In the continually evolving academic sphere, the cultivation of 21st-century abilities has emerged as a pivotal element in ensuring the provision of incredible knowledge of experiences.  This paper scrutinises pioneering pedagogical tactics designed to foster the improvement of 21st-century abilities within the context of quality education. Through examination of present instructional literature and a meticulous evaluation of practical coaching methodologies, this observation endeavours to illuminate powerful teaching strategies that foster critical thinking, ingenuity, collaboration, and virtual literacy among students. Moreover, this examination delves in addition into the position of teachers in fostering those abilities and investigates the ability to demand situations and opportunities linked with the implementation of those processes in diverse academic settings. By exploring the juxtaposition of pedagogy and 21st-century skills, this study aims to offer actionable insights for educators, policymakers, and invested stakeholders eager to cultivate resilient and adaptable learning environments.